Feminist and Intersectional Analysis of Healthcare and Gender Oppression in Alice Walker's Strong Horse Tea: A Feminist Literary Criticism - Hussain, Syed Muzamil; Zahra, Syeda Tehzeeb (Journal of Language and Literature Studies, 2026)
The short story "Strong Horse Tea" by Alice Walker is examined critically in this article through a feminist and intersectional lens.  Set in the mid-twentieth-century rural American South, the short story chronicles the difficult life of Rannie Toomer, a poor Black woman whose frantic attempts to save her ailing child reveal the interconnected effects of class, gender, race, and health care inequalities.  This study, which is based on qualitative textual analysis, uses contextual interpretation, thematic analysis, and close reading to analyze Walker's story. It pays special attention to how systemic neglect, illiteracy, silence, and limited access to education are represented. The theoretical framework draws on feminist literary criticism, intersectionality, and Black feminist thought to interpret her experiences. The analysis shows that Rannie Toomer's repeated physical journeys to seek help symbolize embodied resistance within limited social structures. In contrast, her silence in medical and social settings reflects internalized discrimination shaped by racial and socioeconomic exclusion. By situating the story within the broader tradition of African American women's literature and health humanities scholarship.By showing how mobility, caregiving labor, and silence function as entwined methods of helplessness and resistance in the lives of marginalized women, the article advances Black feminist literary criticism.